A REVIEW ON TASK ALLOCATION PERFORMANCE ISSUES IN CLOUD ENVIRONMENT - Redishettywar, Kavita; Thekiya, Prof. Rafik Juber (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Cloud computing is an emerging paradigm in the computer industry where the computing is moved to a cloud of computers. It has become one of the buzz words of the industry. The core concept of cloud computing is, quite simply, that the vast computing resources that we need will reside somewhere out there in the cloud of computers and we’ll connect to them and use them as and when needed. Computing can be described as any activity of using and/or developing computer hardware and software. It includes everything that sits in the bottom layer, i.e. everything from raw compute power to storage capabilities. Cloud computing ties together all these entities and delivers them as a single integrated entity under its own sophisticated management. Load balancing is a mechanism that distributes the dynamic workload equally across over the nodes or virtual machines within the whole cloud server to avoid a state of conflict wherever some virtual machines are measured as heavily loaded whereas others nodes or hosts are measured as idle or doing very little work. It helps to realize a high client satisfaction and resource utilization magnitude relation, consequently increasing the performance and resource utility of the system. It additionally makes sure that each computing resource in the cloud server is distributed with efficiently and fairly among all the requests of the client. It additionally prevents bottlenecks of the system which can occur because of load imbalance.